Odonata diversity (Anisoptera & Zygoptera) at Purwodadi Botanical Garden, East Java, Indonesia - Khafi, Achmad Muhaimin Nur; Megasari, Dita; Windriyanti, Wiwin; Ningrum, Linda Wige (Agrovigor, 2024)
Dragonflies are one of the insects that have an important role in maintaining the balance of the food chain and the sustainability of the ecosystem. Dragonflies can be used as a natural indicator of the quality of an ecosystem, changes in an environmental ecosystem and to assess the level of environmental damage. Dragonflies can also be used as an indicator of air cleanliness. The aim of this research is to inventory the diversity of dragonfly species (Odonata) in the Purwodadi Botanical Gardens, observe the influence of the environment on the behavior of dragonflies (Odonata), and identify the types of dragonflies in the Purwodadi Botanical Gardens. The inventory method for dragonfly species is carried out using the shipping method which includes direct capture, collection, identification of dragonflies, and data analysis, as well as direct observation. 11 species of dragonflies were found which are members of 6 families, namely Libellulidae, Gomphidae Platynemididae, Chlorocyphidae, Coenagrionidae, Euphaeidae. Diversity of dragonfly types found in 6 locations in the Purwodadi Botanical Gardens area. The results say that the types of dragonflies are not different, showing a close relationship with the ability to adapt to environmental changes. Dragonflies in the Purwodadi Botanical Gardens are included in medium diversity because they are in the range 1H'3 with a value of 1.8. while the Dragonfly Type evenness index shows a value of 0.7, which means high evenness. The results of calculating the distribution of dragonflies show that the overall distribution of dragonflies is regular, except for Euphaea variegata which has a clustered distribution. This research proves that dragonflies have an important role in life, their biological function is as a predator of small insects and as a bioindicator of the quality of an environment.